Training and Assistance for Strengthening of the Early Childhood in Rembang Regency (Indonesian Journal of Early Childhood Education Studies, 2022)
Currently, many institutions that organize PAUD programs only last for 1 to 2 years. This happens because of their lack of knowledge in managing PAUD so that educators and education staff at the institution cannot work professionally. Management plays an important role in all fields, including Early Childhood Education (PAUD). By implementing management processes systematically, all daily activities can run smoothly. Sustainable PAUD management will form a network of cooperation and coordination to assist PAUD managers so that learning activities can run optimally. An educational institution can run effectively and efficiently, it is necessary to have good regulation and management in order to survive in the midst of today's competition. This study aims to improve PAUD management (early childhood education) by identifying systems problems. The method used in this service activity is training and mentoring in order to strengthen the internal management of Umi Fatimah PAUD. The result of this activity is that PAUD Umi Fatimah managers can understand the importance of school management and well-coordinated management will support the achievement of school goals. Keywords: Management, Assistance, PAUD.